Women's experiences of marital rape and sexual violence within marriage in India: evidence from service records. Issue 2 (1st January 2022) - Deosthali, Padma-Bhate; Rege, Sangeeta; Arora, Sanjida
Abstract: Sexual violence within marriage is common and manifests in various forms, including marital rape. It has serious physical and mental health consequences and is a violation of women's sexual and reproductive health rights. Marital rape, reproductive coercion, inserting objects in the vagina or anus, and withholding sexual pleasure are forms of violence routinely experienced by women. Based on service records of survivors coming to public hospitals in an Indian city, this paper presents their pathways to disclosure and institutional responses such as hospitals and police. The findings highlight that a large proportion of survivors of domestic violence confide having experienced forced sexual intercourse by the husband while sharing their experience of physical, economic, and emotional violence with crisis intervention counsellors. However, a small number of women do report marital rape to formal systems like hospitals and police. These systems respond inadequately to women reporting marital rape, as the rape law exempts rape by husband. Sexual violence within marriage can have serious health consequences, and a sensitive healthcare provider can create an enabling environment for disclosing abuse and providing relevant care and support. The paper argues that a necessary precondition to enable women to access health care and justice is to nullify "Exception 2 to Section 375 of the Indian Penal Code" This exception exempts rape by the husband from the purview of the rape law.